Rescuer Exertion and Fatigue Using Two-Thumb vs. Two-Finger Method During Simulated Neonatal Cardiopulmonary Resuscitation - Claire Reynolds; Jennifer Cox; Vicki Livingstone; Eugene Michael Dempsey; Eugene Michael Dempsey (Frontiers Media S.A., 2020)
Background: Rescuer fatigue during neonatal CPR can affect CPR quality leading to reduced cerebral and myocardial perfusion.Aim: To investigate rescuer fatigue during simulated neonatal CPR using both objective (heart rate and cardiac output) and subjective measures.Methods: A randomized crossover manikin study performed. Nineteen doctors working in neonatology were randomized to (a) two-thumb term, (b) two-finger term, (c) two-thumb preterm, or (d) two-finger preterm group. Cardiac output and heart rate were measured with a non-invasive cardiac output monitor. A Likert scale assessed participants' level of perceived exertion.Results: In the preterm group, the mean change in HR from rest to 5 min in the TT group was 11.58 bpm (SD 6.22) vs. 9.94 bpm (SD 8.48), (p-value 0.36). There was no difference in change in CO, 2.10 (SD 1.15) in the TT group vs. 1.39 (SD 1.63) in TF group (p value 0.23). There was no difference in BORG RPE rating. In the term group, the mean change in HR from rest to 5 min was 15 bpm (SD 8.40) in TT group and 13 bpm (SD 7.86) in TF group, (p-value 0.416). The median change in CO from rest to 5 min was 1.50 (0.78 to 2.42 IQR) in TT group vs. 1.60 (0.65 to 3.0 IQR) in TF group.Conclusion: Providing chest compressions is associated with an increase in both heart rate and cardiac output. We did not identify difference between objective and subjective measures of fatigue between either technique in a preterm or term model.